An insight to therapeutic potential and phytochemical profile of Solanum villosum (L) - Kulsoom Zahara; Nabeela Ahmad; Yamin Bibi; Fatima Bibi; Huma Mehreen Sadaf; Nadia Sardar (Elsevier, 2019)
Solanum villosum (L) is a therophyte belonging to family Solanaceae. It is commonly known as red-fruit nightshade, is a brittle-stemmed weed distributed throughout the tropical and temperate regions of the world including Kenya, China, India and Pakistan. S. villosum is a traditionally important plant used in various systems of medicine for the treatment of leucorrhoea, nappy rash, wounds, and cold sore as well as an ointment for sores and abscess. Plant also possess analgesic, antispasmodic, antiseptic, antidysentric, antinarcotic, emollient, diuretic, tonic, soporific, laxative, anticancer, antiulcer, antimicrobial, molluscicidal and antiparasitic activity. S. villosum is rich in various phytochemicals such as alkaloids, flavonoids, saponins, terpenoids, steroids, phenols, tannins, carbohydrates, glycosides, amino acids and proteins responsible for various bioactivities of plant. S. villosum is used as a leafy vegetable and is valued as wild edible supplement diet. It helps in overcoming the deficiency of nutritional constituents and boosting up the immunity of body. This review reveals the detailed exploration of the botany, phytochemistry and pharmacological and nutritional aspects of S. villosum in order to provide a direction for further research.